2011
DOI: 10.1080/13803395.2010.550602
|View full text |Cite
|
Sign up to set email alerts
|

Computerized analysis of error patterns in digit span recall

Abstract: We analyzed error patterns during digit span (DS) testing in four experiments. In Experiment 1, error patterns analyzed from a community sample of 427 subjects revealed strong primacy and recency effects. Subjects with shorter DSs showed an increased incidence of transposition errors in comparison with other error types and a greater incidence of multiple errors on incorrect trials. Experiment 2 investigated 46 young subjects in three test sessions. The results replicated those of Experiment 1 and demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…In the current experiment, 44% of malingering subjects produced abnormal results on the C-TMT-A, and 18% produced abnormalities on the C-TMT-B. As in previous reports [38], malingering-related abnormalities on the TMT were relatively less common than those observed in the same subjects on tests of simple reaction time [44], digit span [45], and finger-tapping [46]. …”
Section: Experiments 3: Effects Of Malingeringsupporting
confidence: 80%
“…In the current experiment, 44% of malingering subjects produced abnormal results on the C-TMT-A, and 18% produced abnormalities on the C-TMT-B. As in previous reports [38], malingering-related abnormalities on the TMT were relatively less common than those observed in the same subjects on tests of simple reaction time [44], digit span [45], and finger-tapping [46]. …”
Section: Experiments 3: Effects Of Malingeringsupporting
confidence: 80%
“…Each CCAB test session included the following computerized tests and questionnaires: finger tapping [73, 74], simple reaction time [75, 76], Stroop, digit span forward and backward [77, 78], verbal list learning, visuospatial span [79, 80], trail making [81], vocabulary, design fluency [82], the Wechsler Test of Adult Reading (WTAR), choice reaction time [75, 83], risk and loss avoidance, delay discounting, the Paced Auditory Serial Addition Task (PASAT) [84], the Cognitive Failures Questionnaire (CFQ) and the Posttraumatic Stress Disorder Checklist (PCL) [85], and a local traumatic brain injury questionnaire. Testing was performed in a quiet room using a standard Personal Computer (PC) controlled by Presentation® software (Versions 13 and 14, NeuroBehavioral Systems, Berkeley CA).…”
Section: Experiments 1 Demographic Influences On Verbal Fluencymentioning
confidence: 99%
“…Subjects reported an average computer-use score of 5.09 (an average of 2–3 hours per day). In previous studies, we found that daily hours of computer-use correlated with performance both on tests that required responding with the mouse [75, 76, 79, 81, 85] and tests that required only verbal output, such as digit span [78] and the paced auditory serial addition test [84]. …”
Section: Experiments 1 Demographic Influences On Verbal Fluencymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still some unresolved issues that need to be addressed, such as the influence of the patient's intellectual level and psychiatric status on PVTs (Avila et al., ; Shandera et al., ). It has also been noted that patients with TBI may have difficulty with PVTs for a myriad of other reasons, including education level, attention impairments, or receptive language impairments (Schroeder, Twumasi‐Ankrah, Baade, & Marshall, ; Woods et al., ).…”
Section: Introductionmentioning
confidence: 99%